The cancer-risk variant frequency among Polish population reported by the first national whole-genome sequencing study - Mroczek, Magdalena; Liu, Jakub; Sypniewski, Mateusz; Pieńkowski, Tadeusz; Itrych, Bartosz; Stojak, Joanna; Pronobis-Szczylik, Bartosz; Stępień, Maria; Kaja, Elżbieta; Dąbrowski, Maciej; Suchocki, Tomasz; Wojtaszewska, Marzena; et al. (Frontiers in Oncology, 2023)
Population-based cancer screening has raised many controversies in recent years, not only regarding the costs but also of the ethical nature and issues related to variant interpretation. Nowadays, genetic cancer screening standards are different in every country and usually encompass only only individuals with a personal or family history of a relevant cancer. Here we performed a broad genetic screening for cancer-related rare germline variants on population data from the Thousand Polish Genomes database based on 1076 Polish unrelated individuals that underwent whole genome sequencing (WGS). We identified 19 551 rare variants in 806 genes related to the oncological diseases, among them 89% have been located in non-coding regions. The combined BRCA1/BRCA2 pathogenic/likely pathogenic according to ClinVar variants in the unselected population of 1076 Poles was 0.42%, corresponding to nine carriers. Altogether, on the population level, we found especially problematic the assessment of the pathogenicity of variants and the relation of ACMG guidelines to the population frequency. Some of the variants may be overinterpreted as disease-causing due to their rarity or lack of annotation in the databases. On the other hand, some relevant variants may have been overseen given that there is little pooled population whole genome data on oncology. Before population WGS screening will become a standard, further studies are needed to assess the frequency of the variants suspected to be pathogenic on the population level and with reporting of likely benign variants.